(untitled) (Praxis Educativa, 2024)
Education is fundamental in learning the necessary skills for the social, economic and cultural development of every nation. The 2030 Agenda establishes in SDG 4, "Ensure inclusive and equitable quality education, and promote lifelong learning opportunities for all" (UNESCO, 2018). Lifelong learning is understood throughout life, and this implies improving the transition processes between educational levels, from primary education to higher education and the labor market, thus generating articulation processes. In Colombia, the articulation of secondary education with higher education has been defined since the General Education Law of 1994. However, one of the biggest challenges in this transition is the articulation of the state university and the productive sector. Clear policies of the Ministry of National Education are necessary, articulation with the labor market and opportunities for technical and technological training.